Stock market liquidity : (J. Wiley & Sons, 2008)
Market microstructure, the study of financial market frictions at a micro level, helps us refine our understanding of what may be driving market liquidity and provides tools to investors of all stripes to profit from this knowledge. In Stock Market Liquidity, editors and financial experts Francois-Serge Lhabitant and Greg Gregoriou bring together the best minds in the business to address this issue and discuss their thoughts on other innovative topics associated with liquidity in today’s markets